Estudo de metabólitos especiais de fungos endofíticos associados à Hyptis suaveolens (L.) Poit. (Lamiaceae) - Silva, Igor Pereira da (2015)
Endophytic fungi are microorganisms that inhabit the interior of plants and, at that particular moment, no visible symptoms of disease in their hosts. These special microorganisms produce metabolites with diverse biological activities. The objective was to isolate and identify special bioactive metabolites of ethyl acetate extract (EtOAc) of endophytic fungi obtained from Hyptis suaveolens L. Poit (Lamiaceae). There are no reports in the literature of bioactivities of endophytic fungi obtained from H. suaveolens. Were collected endophytic fungi from the bank of microorganisms Laboratory of Biotechnology and Microbial Ecology (LABEM), isolated from roots of H. suaveolens. We selected 14 strains: Aspergillus terreus (F7), Botryosphaeria dothidea (F80), Cladosporium flabelliforme (F24), Fusarium oxysporum (F3), Macrophomina phaseolina (F2), Mycoleptodiscus indicus (F21), Neosartorya pseudofischeri (F36), Penicillium chermesinum (F99), Taifanglania biformis (F19), Taifanglania curticatenata (F27), Taifanglania hechuanensis (F34), Thanatephorus cucumeris (F40), Trichoderma koningiopsis (F4) and Uncultured Pleosporales (F97). EtOAc extracts were prepared and conducted tests of antimicrobial, capture of free radical DPPH (2,2-diphenyl-1-picryl-hidrazila), total phenols, schistosomicidal, antidepressant and cytotoxity. The antimicrobial test was performed by the disk diffusion method, minimum inhibitory concentration and minimum concentration of death. In the disc diffusion test were used pathogens Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), E. coli ESBL + and Pseudomonas aeruginosa, the latter two being multiresistant bacteria. The AcOEt extracts of C. flabelliforme (F24), T. biformis (F19) and T. curticatenata (F27) were the most effective in inhibiting E. coli (ATCC 25922). Similarly, the extracts T. biformis (F19) and T.curticatenata (F27) efficiently inhibited S. aureus (ATCC 25923). Inhibition of multidrug-resistant bacteria was less evident, with results similar to those obtained with the control tetracycline. In the minimum inhibitory concentration test, extracts of T. curticatenata (F27), N. pseudofischeri (F36) and T. biformis (F19) inhibited S. aureus (ATCC 25923) at concentrations 30, 80 and 160 µg/mL, respectively. In the minimum concentration of death test, satisfactory results were obtained only in test against S. aureus (ATCC 25923), where all extracts caused death and the minimum concentration of death was the same as the minimum inhibitory concentration. In the capture test of free radical DPPH, the highest activities were obtained with extracts from A. terreus (F7) and T. curticatenata (F27), obtaining 61.73% and 59.44%, respectively. The total phenolic content was quantified by the Folin Ciocalteu method. The highest levels of total phenols were observed in extracts of M. indicus (F21), T. koningiopsis (F4) and B. dothidea (F80), with values of 0.50, 0.49 and 0.48 mg/mL, respectively. The schistosomicidal activity was evaluated according to the reduction of motor activity and mortality of Schistosoma mansoni adult worms. Only the extract of N. pseudofischeri (F36) (100 µg/mL) caused a reduction of motor activity. Extracts of A. terreus (F7) (100 µg/mL) and T. curticatenata (F27) (25 µg/mL) killed 100% of the worms. But the extract of N. pseudofischeri (F36) killed 50% of the worms (200 µg/mL). The antidepressant activity was carried out by the tail suspension test, and only rated the A. terreus (F7) extract. The extract was inactive. The isolation of metabolites was by high performance liquid chromatography (HPLC). From the extract of A. terréus (F7) were isolated terrein (1), butyrolactone V (2), substance (3) andbutyrolactone I (4). From the extract of N. pseudofischeri (F36) was isolated di (2-ethylhexyl) phthalate (5). Their structures were proposed by 1H NMR, 13C, DEPT-135, COSY, HMQC, HMBC and mass spectrometry. The substance (3) is still in the process of elucidation. The isolated compounds were subjected to the cytotoxity, antimicrobial, capture of free radical DPPH, schistosomicidal, trypanocidal, leishmanicidal and antitumor tests. Cytotoxicity was assessed with the extracts from A. terreus (F7) and N. pseudofischeri (F36), and with the isolated compounds, against to the normal line of human lung fibroblasts (GM07492A). Di (2-ethylhexyl) phthalate (5) showed no toxicity, not presenting IC50 in the highest concentration evaluated (5000 µg/mL), and other substances were slightly toxic. At antimicrobial activity only butyrolactone I (4) showed good results, inhibiting and killing E. coli (ATCC 25922) in 50 µg/mL. In the capture test of free radical DPPH, butyrolactone V (2) and butyrolactone I (4) showed 95.12% activity and 95.92%, respectively, higher concentration evaluated (100 µg/ mL) with results similar to ascorbic acid control (95.88%). In schistosomicide test evaluating reduction of motor activity, the terreína (1)reduced motor activity of 75% of the worms, with 100 µg/mL; butyrolactone V (2) reduced 25% with 200 µg/mL; butyrolactone I (4) reduced 25% with 100 µg/mL. In the mortality evaluation, butyrolactone I (4) killed 100% of the worms at 100 µg/mL, and terreína (1) and butyrolactone V (2) killed 100% of the parasites, in 200 µg/mL. In trypanocidal test against Trypanosoma cruzi, substance (3) and di (2-ethylhexyl) phthalate (5) were ineffective. The remaining samples were inactive. The antitumor activity was evaluated against breast cancer cells MDA-MB-231 and MCF-7 by the MTT assay (3-(4,5-metilazol-2-yl) -2,5-diphenyltetrazolium bromide). Against MDA-MB-231, all substances showed strong activity, in which the substance (3) had the best result (IC50 of 5.31 µg/mL). Against MCF-7, butyrolactone I (4) and di (2-ethylhexyl) phthalate (5) were the most active, with IC50 of 7.40 and 7.79 µg/mL, respectively. The antileishmanial activity was tested against Leishmania amazonensis by the MTT method. Di (2-ethylhexyl) phthalate (5)was the most active substance with IC50 of 5.30 µg/mL, followed by the substance (3) with 6.04 µg/mL.